Involvement of ethylene biosynthesis and signalling in fruit set and early fruit development in zucchini squash (Cucurbita pepo L.) - Martínez, Cecilia (BioMed Central, 2013)
BACKGROUND: We have identified a kind of parthenocarpy in zucchini squash which is associated with an incomplete andromonoecy, i.e. a partial conversion of female into bisexual flowers. Given that andromonoecy in this and other cucurbit species is caused by a reduction of ethylene production in the female flower, the associated parthenocarpic development of the fruit suggested the involvement of ethylene in fruit set and early fruit development. RESULTS: We have compared the production of ethylene as well as the expression of 13 ethylene biosynthesis and signalling genes in pollinated and unpollinated ovaries/fruits of two cultivars, one of which is parthenocarpic (Cavili), while the other is non-parthenocarpic (Tosca). In the latter, unpollinated ovaries show an induction of ethylene biosynthesis and ethylene signal transduction pathway genes three days after anthesis, which is concomitant with the initiation of fruit abortion and senescence. Fruit set and early fruit development in pollinated flowers of both cultivars and unpollinated flowers of Cavili is coupled with low ethylene biosynthesis and signalling, which would also explain the partial andromonoecy in the parthenocarpic genotype. The reduction of ethylene production in the ovary cosegregates with parthenocarpy and partial andromonoecy in the selfing progeny of Cavili. Moreover, the induction of ethylene in anthesis (by ethephon treatments) reduced the percentage of bisexual parthenocarpic flowers in Cavili, while the inhibition of ethylene biosynthesis or response (by AVG and STS treatments) induces not only andromonoecy but also the parthenocarpic development of the fruit in both cultivars. CONCLUSIONS: Results demonstrate that a reduction of ethylene production or signalling in the zucchini flower is able to induce fruit set and early fruit development, and therefore that ethylene is actively involved in fruit set and early fruit development. Auxin and TIBA treatments, inducing fruit set and early fruit development in this species, also inhibit ethylene production and the expression of ethylene biosynthesis and response genes. A model is presented that discusses the crosstalk between ethylene and auxin in the control of fruit set and early fruit development in zucchini squash.